Effects of Ingested vs. Injected Propellant on Radio-Frequency Discharge Plasma Properties - Caruso, Natalie R. S.; Walker, Mitchell L. R. (Frontiers in Physics, 2019)
Radio-frequency (RF) ion thrusters are characterized in vacuum test facilities differentiated by pumping speed and thus subject to varying levels of neutral propellant ingestion that affect plasma plume properties and artificially raise the pressure of neutral propellant available to the thruster. These plasma properties are often used to calculate anticipated thrust values for RF thruster prototypes without consideration of the effects ingested neutral propellant may have beyond increasing the amount of neutral atoms available. This study compares exit plane plasma properties for nominal operation of a replica of the Madison Helicon Experiment operating at a propellant flow rate of 2 standard cm^3/min argon subject to 3.8 cm^3/min ingested argon flow with thruster operation over a range of propellant flow rates (1.3–60 standard cm^3/min argon) subject to a maximum ingested argon flow rate of 0.8 cm^3/min to determine the validity of compensating for neutral ingestion at higher operating pressures by increasing supplied propellant flow rates when operating at lower facility pressures. This study finds that no single operating condition at the 0.8 cm^3/min ingestion condition reproduces all the plasma property values recorded at the nominal flow rate at the 3.8 cm^3/min ingestion condition. The inability of plasma properties to be reproduced at a single adjusted flow rate is a result of the differing magnitudes of influence neutral ingestion effects have on individual plume properties.